Investigating effective psychological interventions in pregnant women's sexual satisfaction: A systematic review - Maryam Naji; Seyedeh Zeynab Hoseinnezhad; Farahnaz Heshmat; Negar Asgharipour (Wolters Kluwer Medknow Publications, 2024)
Sexual satisfaction is an important factor in people's lives, which is effective in all aspects of a couple's life. During pregnancy, due to existing changes, sexual performance is affected, which will also change sexual satisfaction. By performing effective interventions, changes can be made in the level of sexual satisfaction. The aim of this study is to investigate effective psychological interventions in the sexual satisfaction of pregnant women, which has been conducted in the form of a systematic review. This study is performed in 2022 with the steps of design of study question, search in SID, PubMed, Magiran, Iran doc, Science Direct, Scopus, and Google Scholar search engine with keywords such as "interventions", "sexual satisfaction", "Sexual function", "couples", "pregnant women" and their English equivalents, and after that, related studies were identified from the period of 2012 to 2022 (the last 10 years), the selection of studies, which after screening the title, abstract, and full text. Among 821 studies, finally 13 studies were left to announce the results. Researches that had unclear sample size and method of implementation and whose full text was not available were initially excluded from the study process. Screening of the quality of the studies was done by the risk assessment checklist and the Jadad Scale of the intervention studies. Then the findings were classified. The results of the present study were taken from 13 articles, which included mindfulness, cognitive-behavioral therapy, therapy based on acceptance and commitment and group counseling, PLISSIT model intervention, and education and support package. As per the results of interventions, all interventions during pregnancy can increase sexual satisfaction in pregnant women. Therefore, such interventions are recommended but it is necessary to do more interventions with minimal bias and long-term follow-up and comprehensive examination of variables to reach stronger evidence.